The Effect of 2015-2019 Government Expenditure in the Education, Health and Purchasing Power Parity Sectors on the Human Development Index (Hdi) of South Halmahera Regency - Sudharma, I Wayan Artadana Adi; D.M., Rustan; D.S., H. Saripuddin (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine and analyze the effect of government spending in South Halmahera Regency in 2015-2019 on the education, health and purchasing power parity sectors on the human development index (HDI). The population is education data, health data, purchasing power parity and human development index (HDI) data in South Halmahera Regency in 2015-2022 which are sampled. The research method uses a quantitative descriptive approach. The results of the study found that: (1) Government spending on the education sector has a positive but insignificant effect on HDI, (2) Government spending on the health sector has a positive but insignificant effect on HDI, (3) Government spending on the community purchasing power sector has a positive and insignificant effect on HDI. (4) Government spending on the education, health and community purchasing power sectors has a positive but insignificant effect on the HDI.